Creative Destruction: Chinese GDP per capita from the Han Dynasty to Modern Times - Kent Deng; Patrick Karl O'Brien (European Historical Economics Society (EHES), 2014)
Our article is a critical survey of the concepts, methods and date constructed and utilized by scholars (particularly the late Angus Maddison) in order to provide estimates for the measurement of relative levels and long term trends in the GDP per capita for China from the Han Dynasty to modern times. We applaud the endeavour but have reluctantly concluded that, even as conjectures, they are not fit for purpose. Furthermore, our article suggests that the Kuznetsian paradigm in empirical economics may not turn out to be viable for qualitative analysis of the long term development of imperial economies of pre-modern East and South Asia.
Keywords: 330